2016
DOI: 10.1186/s12936-016-1127-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and natural selection in the rhoptry-associated protein 1 (RAP-1) of recent Plasmodium knowlesi clinical isolates from Malaysia

Abstract: BackgroundThe Plasmodium rhoptry-associated protein 1 (RAP-1) plays a role in the formation of the parasitophorous vacuole following the parasite’s invasion of red blood cells. Although there is some evidence that the protein is recognized by the host’s immune system, study of Plasmodium falciparum RAP-1 (PfRAP-1) suggests that it is not under immune pressure. A previous study on five old (1953–1962) P. knowlesi strains suggested that RAP-1 has limited genetic polymorphism and might be under negative selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 31 publications
4
13
1
Order By: Relevance
“…This was similar to the results for Pk-1-msp-42 reported by Pacheco et al, (2012) whereby the haplotype diversity of their P. knowlesi-infected orangutan samples was 0.0103 ± 0.0031. In addition, our result was also found to be highly diverse and similar to other P. knowlesi functional genes, such as Pk-DBPαII (Hd: 0.986 ± 0.008; π: 0.013 ± 0.002) (Fong et al, 2014), Pk-RAP-1 (Hd: 0.995 ± 0.009; π: 0.01298 ± 0.00091) (Rawa et al, 2016). However, this diversity was less than previously reported previously for both P. falciparum (see Mehrizi et al, 2008;Zamani et al, 2009;Pan et al, 2010;Viputtigul et al, 2013) and P. vivax (see Dias et al, 2011;Kang et al, 2012), which means that P. knowlesi MSP-142 appears to be less diverse than MSP-142 of P. falciparum and P. vivax.…”
Section: Resultssupporting
confidence: 79%
“…This was similar to the results for Pk-1-msp-42 reported by Pacheco et al, (2012) whereby the haplotype diversity of their P. knowlesi-infected orangutan samples was 0.0103 ± 0.0031. In addition, our result was also found to be highly diverse and similar to other P. knowlesi functional genes, such as Pk-DBPαII (Hd: 0.986 ± 0.008; π: 0.013 ± 0.002) (Fong et al, 2014), Pk-RAP-1 (Hd: 0.995 ± 0.009; π: 0.01298 ± 0.00091) (Rawa et al, 2016). However, this diversity was less than previously reported previously for both P. falciparum (see Mehrizi et al, 2008;Zamani et al, 2009;Pan et al, 2010;Viputtigul et al, 2013) and P. vivax (see Dias et al, 2011;Kang et al, 2012), which means that P. knowlesi MSP-142 appears to be less diverse than MSP-142 of P. falciparum and P. vivax.…”
Section: Resultssupporting
confidence: 79%
“…The nucleotide diversity (π: 0.046 ± 0.011) was found to be high when compared to other P. knowlesi functional genes [3941], considering that most of the haplotypes discovered in this study were unique. A similar observation has also been reported for other merozoite surface antigens such as eba175 , and this suggests that even where functional constraints exist, a range of haplotypes can still occur [45].…”
Section: Discussionmentioning
confidence: 57%
“…Nucleotide diversity (π: 0.046 ± 0.011) for the full length sequence was found to be several times higher compared to other P. knowlesi functional genes such as PkDBPαII (π: 0.012) [39], PkAMA-1 (π: 0.00501) [40] and PkRAP-1 (π: 0.01298) [41]. Diversity for Domain B (π: 0.067 ± 0.025) was found to be higher than that for Domain A (π: 0.039 ± 0.002).…”
Section: Resultsmentioning
confidence: 99%
“…The average pairwise nucleotide diversity per site (π) for Pknbpxa was 0.02186. This nucleotide diversity level is higher than the diversity of some other P. knowlesi functional genes such as PkDBPαII (π = 0.012) [ 23 ], PkAMA-1 (π = 0.00501) [ 24 ] and PkRAP-1 (π = 0.01298) [ 25 ]. Phylogenetic trees constructed using Bayesian method showed that the sequences were divided according to Pknbpxa cluster types (Fig.…”
Section: Resultsmentioning
confidence: 99%